PSYCHOLOGICAL FEATURES OF SELF- GOVERNMENT PERSON AFTER SERVING HIS SENTENCE - Soroka, Anatoliy (PSYCHOLOGICAL JOURNAL, 2016)
In this paper we consider psychological features of a deviant personality ability to arbitrary governing, according to the second part of the proposed earlier systems-complex «self-regulation system of a willed person» [2; 5]. Objective: to determine levels of deviant personality ability to arbitrary government and to analyze the data according to the age groups studied indicators. The studies were conducted at three reintegration centers of homeless in Kharkiv region, of different ownership. The sample consists of the total number - 100 males (first six months after release from punishment). Using «self-regulation system of a willed person» we identified and assessed performance using the technique «capacity for self-governing», developed by M. Peysahov that determines levels of ability to random individual governing (high, medium, low). Thus it was revealed that most of the studied have the low level of development in terms of subscale «Bet», «Targeting», «Рlanning», especially in older subjects and at low subscale «Self» in younger subjects make it difficult the process of resocialization of an individual in society after serving the sentence. This is a characteristic and important feature of psychological deviant personality and he is taken under special control in the course of further appropriate psycho programs related to a deliberate action on deviant personality to the change (where appropriate - form) of a personality traits that determine is antisocial behaviour . The prospect of our further research is to determine the impact, we have created «Рsychological correction programs of social rehabilitation of the person after his release from serving of the sentence».